A Correlational Study of the Relationship between Risk Factors and Gun-Related Delinquency among Urban Female Adolescents. (2018) - McGee, Zina T.; Richeson, Brandy; Ducoste, Mollie; Jones, Carileigh; Nunn, Tandeka
No abstract available